2011
DOI: 10.1002/asia.201100329
|View full text |Cite
|
Sign up to set email alerts
|

Click to Join Peptides/Proteins Together

Abstract: Copper(I) is able to catalyze Huisgen 1,3-dipolar cycloaddition in a "click" fashion. This copper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction presents excellent chemoselectivity and occurs over a widerange of reaction conditions. It shows tolerance to variation in both pH and solvent polarity, thereby facilitating the ligation of peptides and proteins to produce peptidomimetics and synthetic proteins. In addition, the only product formed is a 1,4-disubstituted-1,2,3-triazole moiety, in many aspects r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 66 publications
0
28
0
Order By: Relevance
“…The next series of molecules probed whether the hydrogen bonding acceptor and donor nature of the C-7 carboxylate/amide could be mimicked with triazoles, 32,33 guanidines, or sulfonate. The results of the kinetic studies imply that guanidine groups (as in 6 and 7) are inadequate mimics in this context.…”
Section: Discussionmentioning
confidence: 99%
“…The next series of molecules probed whether the hydrogen bonding acceptor and donor nature of the C-7 carboxylate/amide could be mimicked with triazoles, 32,33 guanidines, or sulfonate. The results of the kinetic studies imply that guanidine groups (as in 6 and 7) are inadequate mimics in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Triazoles were considered due to the facility with which they can be generated by copper-catalyzed “click” reactions between readily available alkyne and azide components, 28,29 but modeling indicated that a triazole ring would interfere with the protein-protein interactions at the interface between NPC1 and NPC2 proteins. We therefore modeled various polyether and amide linkers with the correct linker length to span the 5-Å gap between the binding sites.…”
Section: Resultsmentioning
confidence: 99%
“…In order to establish the optimal experimental conditions for the Cu AAC reaction, it was necessary to standardize (i) amounts of precursors and catalysts, (ii) solvents and their proportions, (iii) reaction time, and (iv) temperature. It has been reported that polar solvents favor the generation of the triazole ring. In attempting to carry out this reaction in polar aprotic solvents such as DMF, ring generation was not observed .…”
Section: Methodsmentioning
confidence: 99%
“…It was established that the Cu AAC reaction proceeds in protic polar solvents such as water:methanol (1 : 1 v/v), using the minimum volumes needed to dissolve the precursors and catalysts . It has been reported that azide and alkyne species in an equimolar ratio (0.012 mmol) are required, while the catalyst (0.031 mmol) will have an excess, to guarantee the reaction at short times . The temperature parameter was adopted from Arnusch et al.…”
Section: Methodsmentioning
confidence: 99%